EXPLORING ETHICAL CONCEPTS IN THE LINGUISTIC PICTURE OF THE WORLD: ACOMPARATIVE ANALYSIS OF ENGLISH AND KARAKALAPAK LANGUAGES (Konferensiyalar | Conferences, 2024)
Language serves as a lens through which we perceive and interpret the world around us. Embedded within linguistic frameworks are ethical concepts that shape our understanding of morality, justice, and human behavior. This article delves into the linguistic landscapes of English and Karakalapak languages to uncover how ethical concepts are reflected and understood within their respective cultural contexts.